Innovative Approaches for Integrating Peace Education into the Pancasila Education Curriculum to Foster School Harmony - Anugrah, Anugrah; Anggraeni, Leni (JED (Jurnal Etika Demokrasi), 2024)
This research explores the integration of peace education in Pancasila Education subjects to create a culture of peace in schools. Using a descriptive-exploratory approach, this study examines the effectiveness of cooperative learning, group discussions, and community-based projects in improving students' social skills and conflict resolution abilities. The results showed that these methods succeeded in reducing aggressive behavior, increasing empathy, and building harmonious relationships between students. Practical implications include the need for teacher training, institutional support, and long-term evaluation to ensure program sustainability. This research offers an integrated model that can be adapted for other educational contexts, supporting efforts to create a peace-loving and harmonious generation.